ASSESSING LEARNING AND BEHAVIORAL OUTCOMES OF THE DHUHA PRAYER HABITUATION PROGRAM USING KIRKPATRICK’S FOUR-LEVEL MODEL: EVIDENCE FROM SMPIT NUR HIDAYAH SURAKARTA - Fadhilla Nangroe Anggraini; Ari Anshori; Muhammad Wildan Shohib; Muhammad Fathi Salim (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Education plays a central role in shaping behavior and enhancing individual knowledge and skills, including in the field of Islamic Religious Education (PAI). Program evaluation serves as a crucial component of the learning process to assess the effectiveness of educational initiatives. This study aimed to evaluate the Dhuha prayer habituation program implemented at SMPIT Nur Hidayah Surakarta by applying Kirkpatrick’s four-level evaluation model, which includes reaction, learning, behavior, and results. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings indicated that the Dhuha prayer habituation program had a positive impact on improving students’ understanding of sunnah prayer materials, fostering behavioral discipline, and cultivating spiritual values in daily life. The application of Kirkpatrick’s model proved effective in providing a comprehensive overview of the program’s success. This study contributes theoretically by reinforcing the relevance of the Kirkpatrick model in evaluating religious and character-based education programs, and practically by offering insights for educators and policymakers in designing holistic Islamic education programs that integrate spiritual and behavioral development.